MANAJEMEN BERBASIS SEKOLAH DI SDN KARANG RAHAYU 01 CIKARANG UTARA BEKASI - Nadya Reza Pratiwi; Amirudin Amirudin; Iqbal Amar Muzaki (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The purpose of this study is to understand and describe the implementation of SBM in improving student learning outcomes at SDN Karang Rahayu 01. The approach used is an approach that makes descriptive data in the form of written or spoken words from participants. The data collection technique used was interviews from all parties in the school from the principal, teachers, students, staff and others. The impact of this research can be explained until the implementation of SBM goes well, then it is known that the implementation or implementation of SBM at SDN Karang Rahayu 01 includes student management, teacher quality management, curriculum management, finance and infrastructure management. To find out student learning outcomes, SDN Karang Rahayu 01 conducted a class evaluation using test and non-test techniques. From the work of SBM in improving student learning outcomes at SDN Karang Rahayu 01, it turns out that the inhibiting and driving factors are. The inhibiting factor encountered by SDN Karang Rahayu 01 was the date of funding and for the driving factor is the involvement and cooperation between parents and teachers in educating students at SDN Karang Rahayu 01. Then the effort to follow up on SBM in improving student learning outcomes at SDN Karang Rahayu 01 is to disseminate information to parents when problems occur